COMPARISON OF SEVOFLURANE VERSUS PROPOFOL FOR TRACHEAL INTUBATION IN CHILDREN - Ali, Zulfiqar; Hussain, Azhar; Malik, Aamer Mahmood; Ahmed, Arslan; Saqib, Mohammad; Qadri, Anjum (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the quality of intubation and hemodynamic response in children undergoing endotracheal intubation facilitated with propofol versus sevoflurane. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesia, Combined Military Hospital Multan, from Aug 2018 to Apr 2019. Methodology: A total number of 112 children planned for tracheal intubation were included in this randomized controlled trial. Patients were randomly allocated into two equal groups. In group P (propofol) patient’s 2.5-3.0 mg/kg propofol was given before insertion of endotracheal tube and in group S (sevoflurane) patients 8.0% sevoflurane with 100% O2. Quality of intubation was assessed in all children at the time of intubation. Hemodynamic response of patients was also noted before induction of anesthesia, immediately after intubation and after 5 minutes of intubation. Results: Mean age of children included in this study was 2.11 ± 0.80 years. Quality of intubation was excellent in 51 (91.1%) patients in propofol group and in 38 (67.9%) patients in sevoflurane group (p-value 0.009). Mean HR after 5 minutes of intubation in group S and group P 111.98 ± 5.43 beats/min versus 109.05 ± 5.99 beats/min with p-value 0.008. Mean arterial pressure after 3 minutes of intubation mean arterial pressure in group S and P was 74.58 ± 4.45 mmHg versus 71.0 ± 3.90 mmHg with p-value <0.001. After 5 minutes of intubation mean arterial pressure in group S and P was 73.16 ± 4.13 mmHg versus 68.61 ± 4.07 mmHg with p-value <0.001. Conclusion: Sevoflurane was found to be associated.........